A meaningful hybrid e-traning measure and model for technology in education - Din, Rosseni; Zakaria, Mohamad Shanudin; Nordin, Mohamad Sahari; Kamarul Zaman, Muhammad Faizal; Abu Kassim, Noor Lide; Tunku Ahmad, Tunku Badariah; Mastor, Khairul Anwar; Abdul Karim, Aidah; Embi, Mohamed Amin (A S E A N Journal of Teaching and Learning in Higher Education, 2011)
A close examination of new hybrid e-training programmes, for determining programme quality, exposed a critical disparity between rapid technological advancements and established pedagogical models. The objective of this study was, therefore, to develop, generate, test, and validate a two-stage model for a meaningful hybrid e-training programme. An early framework of the model helped develop a questionnaire to measure the meaningfulness of a hybrid e-training programme. Confirmatory factor analysis was performed using AMOS 7.0 on data collected from 213 trainees to obtain three best-fit measurement models from three latent variables. Overall reliability analyses, using Cronbach’s Alpha and the Rasch Model, in addition to content validation by experts, suggested that the questionnaire was reliable and valid for measuring a meaningful hybrid e-training programme. Subsequently, structural equation modelling was applied to test the hypotheses. The results showed a strong positive relationship between hybrid e-training and meaningful e-training, a weak positive relationship between learning style preference and hybrid e-training, and a negative relationship between learning style preference and meaningful learning. In brief, the study proved that hybrid e-training contributed significantly towards achieving meaningful learning. Consequently, future training, with respect to the use of hybrid e-training, should include all the five components of meaningful hybrid e-training instead of focusing on the content alone. With the results showing a weak positive relationship between learning style and hybrid e-training, and a negative relationship between learning style and meaningful e-training, instructional media designers and developers should now focus on integrating all the five components of e-training to ensure meaningful learning. It would be interesting to further investigate whether or not learning style is a mediating or a moderating factor in achieving meaningful learning through the use of hybrid e-training programmes, as was modelled in the final results.